2018
DOI: 10.3390/ma11091634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heating Mode and Temperature on the Microstructures, Electrical and Optical Properties of Molybdenum Thin Films

Abstract: In this paper, molybdenum (Mo) thin films are deposited on soda-lime glass (SLG) substrates by direct current magnetron sputtering and heated in three different modes at different temperatures, including substrate heating, annealing treatment, and both substrate heating and annealing treatment. The effects of heating temperature and heating mode on the structures, morphology, optical and electrical properties of Mo thin films were systematically investigated by X-ray diffraction (XRD), Scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This means, based on Scherer formula [22,23], the observed decrease in crystallite size for the exposed RTA sample implies an increase in FWHM, whereas the observed increase in crystallite size for un-exposed RTA sample implies a decrease in FWHM. Additionally, no direct link is observed (based on the microstrain-FWHM formula [24]) between the observed FWHM trend and the samples microstrain decrease for un-exposed and further decrease for exposed RTA samples as compared to un-annealed samples (Table 1). The decrease in crystallite size observed for exposed RTA sample (Table 1) suggests that the sample experienced a substantial nitrogen gas atmosphere, limiting the reaction [25] on the sample and hence reduced its crystallite size.…”
Section: Xrd Analysismentioning
confidence: 94%
“…This means, based on Scherer formula [22,23], the observed decrease in crystallite size for the exposed RTA sample implies an increase in FWHM, whereas the observed increase in crystallite size for un-exposed RTA sample implies a decrease in FWHM. Additionally, no direct link is observed (based on the microstrain-FWHM formula [24]) between the observed FWHM trend and the samples microstrain decrease for un-exposed and further decrease for exposed RTA samples as compared to un-annealed samples (Table 1). The decrease in crystallite size observed for exposed RTA sample (Table 1) suggests that the sample experienced a substantial nitrogen gas atmosphere, limiting the reaction [25] on the sample and hence reduced its crystallite size.…”
Section: Xrd Analysismentioning
confidence: 94%
“…Magnetron sputtering is the most commonly used method for the preparation of Mo films originating from several advantages such as low cost, easy to adjust the parameters, films can be deposited uniformly on large-sized areas [6]. A large number of studies have shown that the structures and properties of Mo films are related to the preparation process and parameters [7][8][9]. For instance, Akçay et al, [10] investigated the effects of deposition pressures and powers on the structures and photoelectric properties of Mo films prepared by radio frequency (RF) magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a higher substrate temperature leads to better crystallinity and thus to larger grains of the film. According to the result of Zhao et al [17], the size of Mo grains varied from 11.7 nm at room temperature to 33.1 nm at 400 • C for 0.3 Pa of the sputtering pressure. The average crystallite size obtained by Su et al [28] was around 8.7 nm at 0.67 Pa. A similar value of grain size (8 nm) was observed in the current studies for a sputtering pressure equaling 1.53 Pa. Small area devices require back contact film with sheet resistance (R s ) about 20 Ω/ [22].…”
Section: Discussionmentioning
confidence: 96%
“…Sputtering power used in these studies was in the range between 0.74 and 1.48 W/cm 2 . The work of [17] presents the dependency of Mo grain size on substrate temperature during the deposition process. It was shown that a higher substrate temperature leads to better crystallinity and thus to larger grains of the film.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation